1970
DOI: 10.1111/j.2042-3306.1970.tb04179.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Laryngeal Hemiplegia in the Horse and Treatment by Abductor Muscle Prosthesis

Abstract: Summary Laryngeal hemiplegia in the horse is discussed regarding incidence and pathologic findings. A hypothesis for its etiology is presented. The clinical and differential diagnosis of the condition is outlined and a new surgical technique, consisting of replacement of the paralyzed crico‐arytenoideus dorsalis muscle by an elastic prosthesis is described. Résumé L'hémiplégie laryngée du cheval est étudiée en fonction des données pathologiques. Une hypothèse étiologique est avancée. Le diagnostic clinique et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
31
0

Year Published

1974
1974
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 7 publications
0
31
0
Order By: Relevance
“…The current standard treatment for RLN is prosthetic laryngoplasty, as described by Marks et al [4], with the goal of permanently abducting the left arytenoid cartilage. This nonphysiological procedure has been modified in recent decades but still has undeniable adverse effects on upper airway health that can be subclinical or clinically apparent [5].…”
Section: Introductionmentioning
confidence: 99%
“…The current standard treatment for RLN is prosthetic laryngoplasty, as described by Marks et al [4], with the goal of permanently abducting the left arytenoid cartilage. This nonphysiological procedure has been modified in recent decades but still has undeniable adverse effects on upper airway health that can be subclinical or clinically apparent [5].…”
Section: Introductionmentioning
confidence: 99%
“…The first prosthetic laryngoplasty was described by Marks et al (1970). This technique is the current standard for treating equine RLN (Kidd and Slone 2002;Dixon et al 2003a;Brown et al 2004) and has a 48-66% success rate in racehorses (Strand et al 2000;Davenport et al 2001;Dixon et al 2001;Kidd and Slone 2002), although a much higher success rate (73-91%) is reported in horses performing at submaximal exercise (Dixon et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of techniques and materials are used to perform prosthetic laryngoplasty in horses. Although polyester is the most widely used suture material, a variety of others have been used, including steel, mersilene, lycra and nylon (Marks et al 1970;Russell and Slone 1994;Tetens et al 1996;Hawkins et al 1997;Davenport et al 2001;Dixon et al 2001;Kidd and Slone 2002;Scherzer and Hainisch 2005). These sutures have differing amounts of elongation at physiological loads, which may affect crosssectional area of the rima glottidis (Cheetham et al 2006).…”
Section: Introductionmentioning
confidence: 99%